Scottish crime and justice survey, 2018-2019: special licence access, victim form data (Scottish Crime and Justice Survey, 2022)
The Scottish Crime and Justice Survey (SCJS) is a social survey which asks people about their experiences and perceptions of crime in Scotland. The survey is an important resource for both the government and public of Scotland. Respondents are selected at random from the Postal Address File and participation in the survey is entirely voluntary. The Scottish Crime and Justice Survey, 2018-2019: Special Licence Access, Victim Form Data study contains data from the Victim Form only. The Main Questionnaire data and all documentation for the SCJS 2018-2019 are available under SN 8795.